2015
DOI: 10.1007/s11095-015-1730-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rous sarcoma Virus-like Particles Displaying hCC49 scFv for Specific Targeted Drug Delivery to Human Colon Carcinoma Cells

Abstract: These results showed that hCC49 scFv-displaying RSV VLPs from silkworm larvae offered specific drug delivery to colon carcinoma cells in vitro. This scFv-displaying enveloped VLP system could be applied to drug and gene delivery to other target cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…79 VLPs based on Rous sarcoma virus displaying the single chain fragment variable (scFv) antibody hcc49 were produced in silkworm larvae and loaded with DOX and demonstrated the ability to kill colon carcinoma cells in vitro . 80 Truncated hepatitis B virus core protein (tHBcAg) loaded with DOX and poly(acrylic acid) demonstrated a sustained drug release profile in vitro in colorectal cancer cells, leading to enhanced antitumor effects. 81 Again, the studies described here and the growing body of data in the literature support the further development and testing of virus-based drug carriers.…”
Section: Resultsmentioning
confidence: 99%
“…79 VLPs based on Rous sarcoma virus displaying the single chain fragment variable (scFv) antibody hcc49 were produced in silkworm larvae and loaded with DOX and demonstrated the ability to kill colon carcinoma cells in vitro . 80 Truncated hepatitis B virus core protein (tHBcAg) loaded with DOX and poly(acrylic acid) demonstrated a sustained drug release profile in vitro in colorectal cancer cells, leading to enhanced antitumor effects. 81 Again, the studies described here and the growing body of data in the literature support the further development and testing of virus-based drug carriers.…”
Section: Resultsmentioning
confidence: 99%
“…7a-c), a known cytokine for therapy against cancers that plays an important role in the regulation of immune cells. 13 The interior of VLP is empty; therefore, we previously demonstrated that RSV VLPs can be packaged with drugs or dyes 17,18 , indicating that the chemotherapeutic drugs cisplatin and dacarbazine can be packaged into RSV VLP-rscFv-rhIL2 and that dual-functional chemotherapeutic agents can be created. In the case of RSV VLP-rscFv-rhIL2 having chemotherapeutic drugs, these drugs can also be specifically delivered to cancer cells expressing TAG-72, mitigating the side effects of chemotherapeutic 286 drugs.…”
Section: Discussionmentioning
confidence: 99%
“…VLP-rscFv-rhIL2s were produced in silkworm by the co-expression of the gag, rscFv and rhIL2 proteins using Bombyx mori nucleopolyhedrovirus (BmNPV) bacmid. To display on the surface of RSV VLPs, rscFv and rhIL2 were anchored using glycophosphoinositol (GPI) 17 and hemagglutinin transmembrane region (HA-TM) 18 , respectively. Each of these anchors can be easily embedded in a lipid bilayer to display the proteins, but here we focus on simultaneously displaying two anchors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, VLPs can be used to deliver therapeutic cargoes to tumours. Similarly, Rous sarcoma VLPs could deliver drugs to colon carcinoma cells [42] and rabbit hemorrhagic disease virus VLPs could deliver gp33 peptide and inhibit the growth of Lewis’ lung carcinoma tumours [43]. Although virosomes and VLPs have proven to be successful vaccines with a potentially improved safety profile, they might not be suitable for all patients as some cancers evolved mechanisms that render them refractory to immunization strategies.…”
Section: A Viral Strategymentioning
confidence: 99%